HiVecMap: A parallel tool for real-time geovisualization of massive geographic vector data - Luo Chen; Zebang Liu; Mengyu Ma (SoftwareX, 2022)
A parallel real-time visualization software tool HiVecMap is proposed here for large-scale geographic vector data mapping. HiVecMap calculates the mapping value of each display cell instead of the value of each vector feature. The mapping value of each display cell is determined by the number of geographic vector features in the corresponding spatial range. Thereby, the computational complexity is depends on the number of the cells rather than the number of features of the whole geographic dataset. When the number of the cells is much smaller than the number of geographic features, the visualization efficiency can be greatly improved. HiVecMap is implemented with the MPI+OpenMP parallel strategy, and has been extensively tested. Results show that large-scale geographic vector data can be online mapped in real-time, which has a performance improvement of more than ten times compared with the existing best methods.